PENDAPATAN ASLI DAERAH UNTUK PEMBANGUNAN DAERAH YANG BERKELANJUTAN DI INDONESIA - Nova Yarsina (Ensiklopedia Social Review, 2020)
This objective is to examine the original income of the region for sustainable regional development in Indonesia, using normative legal research. Regional government finance is a very decisive factor in the administration of regional government. The financial capacity of a region is determined by the existence of a source of regional income and its level of lucrative. The level of a local source of revenue is determined by the extent to which the basis for imposing taxes is responsive to inflation, population growth and economic growth. Generally in developed countries that implement decentralization policies tend to give greater authority to the regions to manage sources of revenue that are lucrative. On the other hand, in developing countries, financial resources are controlled by the central government. Local governments only manage financial resources that are less potential.